2023
DOI: 10.1038/s41598-023-29313-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stable radon fluoride molecules and geometry optimization using first-principles calculations

Abstract: Noble gases possess extremely low reactivity because their valence shells are closed. However, previous studies have suggested that these gases can form molecules when they combine with other elements with high electron affinity, such as fluorine. Radon is a naturally occurring radioactive noble gas, and the formation of radon-fluorine molecules is of significant interest owing to its potential application in future technologies that address environmental radioactivity. Nevertheless, because all isotopes of ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Practicing chemists generate EPMs from experimental data and use the resulting model to detect high reactivity within a molecule. Examples of this are included in the popular journal Nature in which several articles were published using EPMs during the year this paper was written (Jain et al, 2023;Kang et al, 2023;Shalaby et al, 2023). Being able to interpret and utilize EPMs is becoming an essential skill of a practicing chemist and should be considered as a part of student training.…”
Section: Discussionmentioning
confidence: 99%
“…Practicing chemists generate EPMs from experimental data and use the resulting model to detect high reactivity within a molecule. Examples of this are included in the popular journal Nature in which several articles were published using EPMs during the year this paper was written (Jain et al, 2023;Kang et al, 2023;Shalaby et al, 2023). Being able to interpret and utilize EPMs is becoming an essential skill of a practicing chemist and should be considered as a part of student training.…”
Section: Discussionmentioning
confidence: 99%
“…Fitzsimmons and Klobukowski 11 examined a family of organic xenon and radon fluorides and showed that Rn species were thermodynamically more stable than the Xe congeners. Recently, a study has been published by Um and coworkers 12 where their best estimation of the formation enthalpy for RnF 6 was −584 kJ mol −1 , whereas for XeF 6 , the value was −264 kJ mol −1 . In contrast to the oxides, it appears that the fluorides of radon and xenon are generally exergonic.…”
Section: Discussionmentioning
confidence: 99%
“…The chemistry of radon may be rich and varied, and there are promising indications [7][8][9][10][11][12] that this is the case. Fitzsimmons and Klobukowski 11 examined a family of organic xenon and radon fluorides and showed that Rn species were thermodynamically more stable than the Xe congeners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine, characterized by its remarkably high IP, can offset the excitation energy of noble gas electronic configurations, allowing for the formation of noble-gas fluorides. Indeed, species such as KrF 2 , XeF 2 , and RnF 2 are among the most renowned compounds involving noble gases . Notably, they represent a rare category of symmetric insertion compounds with noble gases, with RnF 2 being the only radon compound experimentally reported.…”
mentioning
confidence: 99%